2018
DOI: 10.31104/jsab.v2i2.60
|View full text |Cite
|
Sign up to set email alerts
|

Factors (Benefits, Trust, Self-Efficacy, Ease of Use, Security) Affecting Consumer’s Perception on E-Money in Indonesia

Abstract: This research based on the developments of technology on payment system which replaced the use of cash as a medium of exchange into the non-cash system. The use of e-money as a non-cash system was made to actualize less cash society by the increase of the use of instrument and non-cash channel. However, the government had made a rule by required various costs to use e-money. As the used of e-money seemed forced by a rule, therefore, costumers might have a bad perception toward it. Hence, this research m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
2
2
0
4
Order By: Relevance
“…So that the factors that encourage respondents to use the application are less affected by the behavior of being automatic in using the application, such as using a payment system through payment in various conditions. This result is also supported by previous findings (Pratiwi et al, 2018 ) who concluded that confidence in using electronic payments did not affect their use. Thus, the tenth hypothesis (H10) is not proven and rejected in this study.…”
Section: Influence Of Habit On Use Behavioursupporting
confidence: 89%
See 1 more Smart Citation
“…So that the factors that encourage respondents to use the application are less affected by the behavior of being automatic in using the application, such as using a payment system through payment in various conditions. This result is also supported by previous findings (Pratiwi et al, 2018 ) who concluded that confidence in using electronic payments did not affect their use. Thus, the tenth hypothesis (H10) is not proven and rejected in this study.…”
Section: Influence Of Habit On Use Behavioursupporting
confidence: 89%
“…The results of this analysis are supported by previous research that has been done (Fauz et al , 2018) which revealed that Behavioral significantly affects use behavior. This result is also supported by the findings (Pratiwi et al,2018) which concludes that Behavioral Intention has a significant direct effect on Use Behavior . Thus, the eleventh hypothesis (H11) is proven and accepted in this study.…”
Section: The Effect Of Behavioural Intention On Use Behavioursupporting
confidence: 76%
“…Factors consisting of benefits (X1), trust (X2), self-efficacy (X3), ease of use (X4), and security (X5) have a significant influence on consumer perceptions (Y) 58.3%. This result reflects that these five factors are considered important because become the reason consumers use e-money in Indonesia (Pratiwi & Dewi, 2018).…”
Section: Introductionmentioning
confidence: 67%
“…Penelitian ini sejalan dengan yang dilakukan oleh (Teoh et al, 2013) dan (Pratiwi & Dewi, 2018) yang menunjukkan bahwa tingkat keamanan tidak berpengaruh secara positif terhadap penggunaan sistem pembayaran elektronik.…”
Section: Security Terhadap User Perception Of Electronic Payment Systemunclassified